Determination of Power Requirements for Industrial Enterprise Lighting - V. B. Kozlovskaya; V. N. Radkevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a method for calculation of power expenditure required for industrial enterprise lighting. Method has been proposed that assumes distribution of annual power requirements in quarters with due account of mean value of night-time duration. The paper contains analytical dependences that make it possible to determine a turn-on time of lighting equipment for a calculated period. Their application improves accuracy pertaining to calculation of power expenditure for artificial lighting of industrial enterprises.